Solar Heater System Implementation As A Front Step In Overcoming The Global Warming Issues : Case Studies In Seberang Perai Selatan, Penang. - Lee, Li Li; Abdullah, Aldrin (2008)

(untitled)
The major purpose of this study on solar heater system implementation in Seberang Perai Selatan, is to identify the level of preference and satisfaction from questionnaires answered by the respondents ( the residents equipped with the solar heater system package) and the residents who stay around the case studies area, on the implementation solar heater in the residential housing properties.